Physiochemical properties and tastes of gels from Japanese Spanish mackerel (Scomberomorus niphonius) surimi by different washing processes. Issue 6 (19th September 2018) - Pan, Jinfeng; Jia, Hui; Shang, Meijun; Xu, Chang; Lian, Hongliang; Li, Haowei; Dong, Xiuping
Abstract: The study investigated the properties of gels from Japanese Spanish mackerel ( Scomberomorus niphonius ) (JSM) surimi received conventional washing (CW) or alkaline‐saline washing (AW) and un‐washing (UW). AW gel exhibited the highest breaking force and deformation as well as water‐holding capacity, but CW gel only had higher breaking force than UW gel. Low‐field NMR analysis showed that peak P22 in AW gel was shifted to higher relaxation time and the areas of peak P21 and P22 in AW gel were higher than those in UW and CW gels. Compared with UW gel, network structure of AW gel was more continuous with many tiny voids, but CW gel microstructure showed partially uneven area with large voids. SDS‐PAGE showed that band intensity of myosin heavy chain attenuated more in AW gel than in UW and CW gels in nonreducing electrophoresis and it recovered more pronounced in reducing electrophoresis. Solubility attributed to hydrophobic interaction, hydrogen and disulfide bonds increased in CW and AW gels. AW gel gave stronger bitterness and aftertaste A while CW gel showed heavier sourness, astringency, and aftertaste B than UW gel. Results suggest that AW improved physiochemical properties of gel and preserved a closer taste pattern to UW gel. It is recommended for JSM surimi producing. Practical applications: Surimi food has great potential due to its convenience, elasticity, and nutritional value. Japanese Spanish mackerel (JSM), a popular fish species in China, is widely used for producing surimi food, such as fish ball, dumpling, and sausage. Washing is a practical way to improve its gel properties. This study investigated the gel strength, water status, protein pattern, molecular interactions, microstructure, color, and taste of gels from JSM surimi received conventional washing or alkaline‐saline washing and un‐washing. Some practical information of effects of washing on gel properties was obtained. These results provide supports to the gel properties improvement by appropriate washing for JSM.